Peran baitul hikmah dalam mengembangkan pendidikan islam pada masa dinasti abbasiyah - Abid, Moh. Khusnul; Purnomo, Purnomo (Majelis Pembinaan Kader Sumber Daya Insani Pimpinan Daerah Muhammadiyah Kota Salatiga, 2022)
The role of Baitul Hikmah of the Abbasid dynasty in the development of Islamic education can be seen in several ways: (1) Baitul Hikmah as a library that accommodates a collection of books and manuscripts by scholars; (2) Baitul Hikmah as a center for translating foreign language written works converted into Arabic; (3) Baitul Hikmah as an educational institution in which there are scientific discussions and science teaching classes; (4) Baitul Hikmah as an astronomical observatory that studies stars and scientific studies; and (5) Baitul Hikmah as a center for studies and essays. The authors of the books were given permission by the caliph to conduct studies and author books there. This made it easier for the caliph to monitor the activities of the ragers. But when the Mongols invaded Baghdad, they burned the city of Baghdad and burned the books in the Jerusalem of Wisdom until they were gone. Baitul Hikmah was razed to the ground until there was nothing left.